Performan Ayam Broiler yang Diberi Ransum yang Mengandung Bungkil Kelapa yang Difermentasi Ragi Tape Sebagai Pengganti Sebagian Ransum Komersial - Budiansyah, Agus (Fakultas Peternakan Universitas Jambi, 2010)
The objective of the research was to study effect of using fermented copra meal with ragi tape in ration to replace of commercial feed diets on broiler performance. One hundreds of broiler Lohman strain aged a week were randomly assigned to five dietary treatments. The treatments were consisted of two levels of copra meal without fermentation (BKTF) and two levels of copra meal with fermentation of ragi tape (BKFRT) to replace of part of commercial feed diets (RK) and one of dietary treatment was without copra meal as a control. They were R0 = 100 percent of commercial feed diets as a control (RK); R1 = 10 percent of BKTF + 90 percent of RK; R2 = 20 percent of BKTF + 80 percent of RK; R3 = 10 percent of BKFRT + 90 percent of RK; dan R4 = 20 percent of BKFRT + 80 percent of RK. The chicks were fed for four weeks. At the end of experiment, two broilers from each units were slaughtered to measure carcass weight. Data from completely randomized design were subjected to ANOVA and different among treatments were further analyzed using Tukey test. Parameters of the research were feed consumption, average body weight gain, feed conversion, final body weight and carcass weight. The result of the experiment showed that using of copra meal with or without fermentation used ragi tape in broiler diets to replace commercial feed diets were no significant effect on feed consumption, average body weight gain, final body weight and carcass weight, but they had signifacant effect on feed conversion. Using of copra meal in broiler diets with or without fermentation of ragi tape (BKFRT and BKTF) at level of 20 percent were increase feed conversion. The result concluded that using copra meal in broiler diets with or without fermentation of ragi tape could application at level of 10 percent to replace commercial feed diets, and fermentation of copra meal used of ragi tape had no significant improvement on broiler performance.